Competitiveness of Polish regional Agro-clusters - Bronisz, Urszula; Heijman, Wim (Applied Studies in Agribusiness and Commerce, 2008)
The present paper concerns the analysis and evaluation of the performance of regional agro-clusters in Poland and also the examination of the significant basic factors which have influence on it. The objective of the paper is both to rank the 16 Polish regions according to their competitive position in the agrocomplex and to present their economic and social position, show differences and regional contrasts. Also, we compare the outcomes with the overall Polish regional competitive index, which was created in accordance with the Huggins Institute approach.